Hierarchical AAA in mobile IPv6 networks - XIAO Wen-shu 1; ZHANG Yu-jun 1; LI Zhong-cheng 1 (Tongxin xuebao)
There are many problems of integrating AAA with mobile IPv6 in the next generation Internet.A new hierarchical AAA architecture was proposed to handle these problems.The combined authentication-registration procedure,and the local security association（SA） negotiation were performed to enhance the performance of AAA combined mobility.The proposal is proved to be no less secure and more efficient than the scheme proposed by IETF.